STAND AT EASE/GARY GREEN - Van der Westhuizen, Gert (Scientia Militaria - South African Journal of Military Studies, 2011)
Books by ex-conscripts detailing their experiences were few and far between in the era of the Border War while more than 500 000 white males were called up for what was described as “national service”. While books like these are not exactly flooding the shelves of bookstores, they roll of the presses more regularly now. These works mostly deal with ex-conscript’s that actively experienced the war in Namibia and Angola. Stand at ease is different: there is no "cordite and conflict". Green describes himself as a reluctant conscript (one wonders how many of the erstwhile national servicemen were of the same view). He was a product of one of the country’s first multi-racial schools - in this case a school that did not subscribe to the former government’s apartheid policies. Hence, his period of national service was seen as a necessary evil, something that had to be done - to get it behind one. But he and a few friends were determined to have as easy a time as possible. Their most important aim was to avoid the "dreaded" call-up to the Border. Green was helped in this endeavour when he was medically classified as G3K3. He was called up to 5 South African Infantry Battalion in Ladysmith where he spent a few days before going to Kimberley. He did guard duty at 93 Ammunition Depot in Jan Kempdorp in the Northern Cape before being deployed to the Army Battle School in Lohatla where he spent the rest of his days as a national serviceman. He says his time in the military "could hardly be described as constructive or enjoyable", but it was also "a period of unprecedented personal growth and selfdiscovery”. “There is little doubt that during the two years of my conscription, I stopped being a boy and at some point became a man." Green unfortunately does not elaborate too much on this rite of passage.